Polycystic ovary syndrome, adipose tissue and metabolic syndrome - Delitala, Alessandro P.; Capobianco, Giampiero; Delitala, Giuseppe; Cherchi, Pier Luigi; Dessole, Salvatore (Archives of gynecology and obstetrics, 2017)
Purpose Polycystic ovary syndrome (PCOS) is the most common endocrine disorder that affects women of reproductive age and is characterized by ovulatory dysfunction and/or androgen excess or polycystic ovaries. Women with PCOS present a number of systemic symptoms in addition to those related to the reproductive system. It has been associated with functional derangements in adipose tissue, metabolic syndrome, type 2 diabetes, and an increased risk of cardiovascular disease (CVD). Methods A detailed literature search on Pubmed was done for articles about PCOS, adipokines, insulin resistance, and metabolic syndrome. Original articles, reviews, and meta-analysis were included. Results PCOS women are prone to visceral fat hypertrophy in the presence of androgen excess and the presence of these conditions is related to insulin resistance and worsens the PCO phenotype. Disturbed secretion of many adipocyte-derived substances (adipokines) is associated with chronic low-grade inflammation and contributes to insulin resistance. Abdominal obesity and insulin resistance stimulate ovarian and adrenal androgen production, and may further increase abdominal obesity and inflammation, thus creating a vicious cycle. Conclusion The high prevalence of metabolic disorders mainly related to insulin resistance and CVD risk factors in women with PCOS highlight the need for early lifestyle changes for reducing metabolic risks in these patients.